KAJIAN PENGEMBANGAN EKSPOR KAYU LAPIS INDONESIA KE JEPANG - Kirsfianti L Ginoga; Rachman Effendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Precently non-oil export development is very important for Indonesia's economy. This study is to analize, Indonesia's plywood export development, in particular to Japan, and to discuss some factors which are supposed to influence it.In line with the fast growth of plywood industry in Indonesia there is diversification of export markets. Plywood export to Japan goes on to increase, and now 80% of the Japan's total plywood import come from Indonesia.The result of this study shows that market potential of Indonesia's plywood to Japan large enough, especially if it is perceived from the number of population of age 15 years and up (Xl), where the regression coefficient has shown that each increase of 1000 people in the population of age 15 years and up would increase the Indnoesia 's plywood export for around 50 m3. But there is some c;on traints which suppress the market potential, among other things are Japan's plywood production, consumers preference and government's protective policy. The market share of Indonesia's to Japan can be increased if the constraints are relaxed.